Ferroptosis-related exosomal non-coding RNAs: promising targets in pathogenesis and treatment of non-malignant diseases - Zhang, Yiping; Xie, Jun (Frontiers in Cell and Developmental Biology, 2024)
Ferroptosis, an iron-dependent form of programmed cell death, introduces a novel perspective on cellular demise. This study investigates the regulatory network of exosomal non-coding RNAs (ncRNAs), including miRNAs, circRNAs, and lncRNAs, in ferroptosis modulation. The primary goal is to examine the pathological roles of ferroptosis-related exosomal ncRNAs, particularly in ischemic reperfusion injuries. The research reveals intricate molecular interactions governing the regulatory interplay between exosomal ncRNAs and ferroptosis, elucidating their diverse roles in different non-malignant pathological contexts. Attention is given to their impact on diseases, including cardiac, cerebral, liver, and kidney ischemic injuries, as well as lung, wound, and neuronal injuries. Beyond theoretical exploration, the study provides insights into potential therapeutic applications, emphasizing the significance of mesenchymal stem cells (MSCs)-derived exosomes. Findings underscore the pivotal role of MSC-derived exosomal ncRNAs in modulating cellular responses related to ferroptosis regulation, introducing a cutting-edge dimension. This recognition emphasizes the importance of MSC-derived exosomes as crucial mediators with broad therapeutic implications. Insights unveil promising avenues for targeted interventions, capitalizing on the diverse roles of exosomal ncRNAs, providing a comprehensive foundation for future therapeutic strategies.